Experimental evaluation of the biotic potential and other biological variables of toxocara cati (schrank 1788): a preliminary experiment - Radman, Nilda (2011)
The zoonotic parasite Toxocara cati (Schrank, 1788) is a nematode for domestic cats that also infects humans, with the soil being the principal common reservoir. T. cati, along with other Toxocara species plus Ascaris suum and Baylisascaris procionis, are causative agents of larva-migrans syndrome. Our aim was to determine experimentally the following biological variables for T. cati: time of egg development, prepatent period, and biotic potential. Two cats were inoculated: one with infective T.-cati eggs (IE), the other with mouse meat after deliberate T.-cati infection (M). Quantitative data were compared by the Bayesian mean-differences test and expressed as mean ± standard error. Complete egg development through the infective stage required 23 days; the prepatent period lasted 23 days in both animals; and the mathematically calculated biotic potentials obtained were lower than the values previously reported. Significant differences were observed in the distribution of the mean of eggs/female/day in favor of the M animal (M = 10,033 ± 1,281, vs. IE = 8,599 ± 937, Z = 3.620; P <0.01). The nematodes parasiting the IE cat showed a much more prolonged oviposition than the M that extended until the day after the administration of an antihelminth drug (piperazine). The M animal had stopped oviposition 15 days before that point. Nevertheless, at final of the experience (67 days postinoculation) the eggs per g for the M cat was higher than for the IE. Future studies will elucidate which mode of infection is more significant epidemiologically. Further investigations on the biology of T. cati are needed to enable an efficient epidemiological control of this zoonotic parasite.